Carbon aerogel as a solid-phase microextraction fiber coating for the extraction and detection of trace tetracycline residues in food by coupling with high-performance liquid chromatography. Issue 3 (6th January 2021) - Dong, Zong-Mu; Cheng, Lu; Sun, Tong; Zhao, Guang-Chao; Kan, Xianwen
Abstract : An efficient SPME method using the carbon aerogel as fiber coating was developed for tetracycline detection, and the performance parameters of the analysis are optimized via the BBD software. Abstract : A direct immersion solid-phase microextraction method for determining tetracyclines (TCs) was developed by coupling with high-performance liquid chromatography. A carbon aerogel (CA) was synthesized as a fiber coating with high extractive properties and a low density of 0.1855 g cm −3 via ambient pressure drying and carbonization. The as-synthesized CA exhibited a high specific surface area and a cross-linked structure; it was characterized via scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy and Brunauer–Emmett–Teller analysis, etc. The extraction performance for six TCs was investigated, and the main experimental parameters were optimized by the Box–Behnken design. Adsorption kinetics, Langmuir and Freundlich models were used to clarify the extraction mechanism. This method showed wide linear ranges of 1–500 μg L −1, low limits of detection of 0.52–1.05 μg L −1, good repeatability of 1.37–12.47%, and satisfactory inter-fiber reproducibility of 8.51–15.81% relative standard deviation for the detection of six TCs. Moreover, this study provided an interesting insight into the detection of TCs residues in food samples.